Deep-time gene expression shift reveals an ancient change in avian muscle phenotypes. - Christina M Harvey; Matthew J Fuxjager; James B Pease (PLoS Genetics)
Gene duplication is an important process of molecular evolutionary change, though identifying these events and their functional implications remains challenging. Studies on gene duplication more often focus on the presence of paralogous genes within the genomes and less frequently explore shifts in expression. We investigated the evolutionary history of calsequestrin (CASQ), a crucial calcium-binding protein in the junctional sarcoplasmic reticulum of muscle tissues. CASQ exists in jawed vertebrates as subfunctionalized paralogs CASQ1 and CASQ2 expressed primarily in skeletal and cardiac muscles, respectively. We used an enhanced sequence dataset to support initial duplication of CASQl in a jawed fish ancestor prior to the divergence of cartilaginous fishes. Surprisingly, we find CASQ2 is the predominant skeletal muscle paralog in birds, while CASQ1 is either absent or effectively nonfunctional. Changes in the amino acid composition and electronegativity of avian CASQ2 suggest enhancement to calcium-binding properties that preceded the loss of CASQ1. We identify this phenomenon as CASQ2 "synfunctionalization," where one paralog functionally replaces another. While additional studies are needed to fully understand the dynamics of CASQ1 and CASQ2 in bird muscles, the long and consistent history of CASQ subfunctions outside of birds indicate a substantial evolutionary pressure on calcium-cycling processes in muscle tissues, likely connected to increased avian cardiovascular and metabolic demands. Our study provides an important insight into the molecular evolution of birds and shows how gene expression patterns can be comparatively studied across phylum-scale deep time to reveal key evolutionary events.